Minimally invasive fetal autopsy using ultrasound: a feasibility study. (5th December 2018) - Votino, C.; Cos Sanchez, T.; Bessieres, B.; Segers, V.; Kadhim, H.; Razavi, F.; Condorelli, M.; Votino, R.; D'Ambrosio, V.; Jani, J.
Abstract: Objectives: To evaluate postmortem ultrasound (PM‐US) for minimally invasive autopsy, and to demonstrate its feasibility, sensitivity and specificity, as compared with conventional autopsy, in detecting major congenital abnormalities. Methods: Over a 19‐month study period from 1 March 2012 to 30 September 2013, we recruited from a referral hospital 88 consecutive fetuses, at 11–40 weeks' gestation, which had undergone termination, miscarriage or intrauterine fetal death. We performed PM‐US using different transducers and compared the data with those from conventional autopsy. The latter was performed, according to the Societé Francaise de Foetopathologie (France) guidelines, by experienced perinatal pathologists who were blinded to the ultrasound data. Results: Complete virtual autopsy by ultrasound was possible in 95.5% of the cases. The sensitivity of PM‐US for detecting brain abnormalities was 90.9% (95% CI, 58.7–99.8%) and the specificity was 87.3% (95% CI, 75.5–94.7%). In 20% of cases, a neuropathological examination was not possible due to severe maceration. The sensitivity for detection of thoracic abnormalities was 88.9% (95% CI, 65.3–98.6%) and the specificity was 92.8% (95% CI, 84.1–97.6%), and the sensitivity for detection of abdominal anomalies was 85.7% (95% CI, 57.2–98.2%) and the specificity was 94.6% (95% CI, 86.7–98.5%). Conclusion: This pilot study confirms the feasibility of PM‐US for virtual autopsy as early as 11 weeks' gestation. This new technique shows high sensitivity and specificity in detecting congenital structural abnormalities as compared with conventional autopsy. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.